A novel method to eliminate the symmetry dependence of fiber coils for shupe mitigation - Tugba Andac Senol; Onder Akcaalan; Aylin Yertutanol; Ekmel Ozbay (Scientific Reports, 2024)
Abstract It is a well-known fact that interferometric fiber optic gyroscopes (IFOGs) are easily distorted by thermal effects and distortion results in the degradation of the performance of these sensors. Changing the fiber coil geometry, increasing the winding symmetry, adding fiber buffer layers around the fiber coil, using different modulation methods for multifunctional integrated optic chips, and using special types of fibers, such as photonic crystal fibers, are some alternative solutions for preventing this degradation. This paper, theoretically and experimentally, investigates not only how different types of fiber coil winding methods behave under different rates of temperature change but also presents a novel method, to the best of our knowledge, to eliminate the Shupe effect, without violating the simplest IFOG scheme. This method rules out the importance of the winding symmetry epochally and the need of any extra treatment for the fiber coil to increase the thermal performance of the system. Regardless of the symmetry of the fiber coil winding, the rate error due to the Shupe effect can be reduced to about $$± 0.05^° /$$ ± 0 . 05 ∘ / h for any rate of temperature change with this new method according to the experimental results.